Audit Sistem Informasi Aplikasi DPLK Capital Life Indonesia Menggunakan Framework Cobit 5 - Budyanto, Arifin; Eva Zuraidah (STMIK Budi Darma, 2024)
Information system audits are carried out to identify and ensure that existing system procedures in the company are functioning properly, using the Cobit 5 framework to audit the DPLK Capital Life Indonesia application information system because previously there has never been a comprehensive audit of the information system used by the company so that the information system operational services cannot be ascertained whether or not they are in accordance with the standard needs of the company. With the information system audit on the DPLK Capital Life Indonesia application system running in the company, it is hoped that it can harmonize the needs with the objectives of the company. The research was collected with quantitative capability analysis. The audit results with the highest value, namely the DSS01 domain, get a Maturity Level value of 2.97 with a Fully Achieved achievement value and a gap value of sub domain DSS01.01 gap value of -0.01, DSS01.02 gap value of 0.08, DSS01.03 gap value of -0.01, DSS01.04 gap value of -0.06 and DSS01.05 gap value of -0.08 from target level 3. While the DSS02 domain gets a Maturity Level value of 2.13 with a Fully Achieved achievement value and a sub domain gap value of DSS02.01 gap value of 0.19, DSS02.02 gap value of 0.11, DSS02.03 gap value of 0.19, DSS02.04 gap value of 0.15, DSS02.05 gap value of 0.10, DSS02.06 gap value of 0.10 and DSS02.07 gap value of 0.05 from target level 2. The GAP analysis result obtained from DSS01 and DSS02 have not reached the target level.